Sensitivity of cervical cytology in endometrial cancer detection in a tertiary hospital in Spain. (4th September 2021) - Frias‐Gomez, Jon; Tovar, Eva; Vidal, August; Murgui, Lluis; Ibáñez, Raquel; Peremiquel‐Trillas, Paula; Paytubi, Sonia; Baixeras, Nuria; Zanca, Alba; Ponce, Jordi; Pineda, Marta; Brunet, Joan; et al.
Abstract: Introduction: Cervical cytology is a well‐stablished cervical cancer screening method. However, due to the anatomical continuity of the genital tract, it can also detect signs of endometrial disease. Our aim was to estimate the sensitivity of cervical cytology in endometrial cancer detection and prognosis in a large population over a 30‐year period in a large academic tertiary hospital in Spain. Methodology: We performed a search for women diagnosed with endometrial cancer from 1990 to 2020, who were surgically treated and had a previous cervical cytology result. Information Technologies Department databases from Bellvitge University Hospital and the Screenwide case–control study's database were used. Cervical cytology results were classified as abnormal when squamous lesions, glandular atypia or malignant cells were identified. Results: Overall, we evaluated 371 women with endometrial cancer and a documented cervical cytology performed within 3 years previous to surgical treatment. Overall, the sensitivity of cervical cytology for endometrial cancer detection was 25.6%. Several clinico‐pathological characteristics, such as non‐endometrioid histology and a higher stage, were correlated with higher sensitivity. Discussion: We observed a low sensitivity of cervical cytology to effectively diagnose endometrial cancer. However, recent technological advances using genomics and epigenomics may offer a promising perspective to detect endometrial cancer with high sensitivity in these cervical specimens. Abstract : Cervical cytology sensitivity for endometrial cancer was 25.6%. Several clinico‐pathological factors, such as non‐endometrioid histology and a higher stage, were correlated with higher sensitivity.